Gaya Bahasa dalam Cerpen “Mereka Bilang Saya Monyet” Karya Djenar Maesa Ayu dan Implikasinya terhadap Pembelajaran Bahasa Indonesia Fase F - Anshori, Irham Thufani; Wahyuni, Tri; Raharjo, Resdianto Permata; Darni (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the language style in Djenar Maesa Ayu's short story "Mereka Bilang Saya Monyet" and explore its implications for Indonesian language learning in Phase F. This research employs a descriptive qualitative method with a textual analysis approach and a survey on student interest. The findings reveal that language styles such as metaphor, symbolism, irony, hyperbole, and repetition are strategically used to convey themes of dehumanization, trauma, and exploitation. This research is conducted in SMA A. Wahid Hasyim Jombang. The results highlight that the utilization of language style enhances students' critical thinking, interpretative skills, and aesthetic appreciation. Furthermore, most students demonstrated high interest in learning through this short story, although some struggled with its complex language style. The study concludes that this short story holds substantial potential as a critical literacy-based learning medium relevant to modern students' needs. Further research is recommended to develop adaptive teaching methods utilizing similar-themed literary works to enrich learning materials.